Dataset 1: Flexoelectro-optic liquid crystal analog phase-only modulator with a 2𝜋 range and 1 kHz switching - Fells, J; Wang, X; Elston, S; Welch, C; Mehl, G; Booth, M; Morris, S (University of Oxford, 2018)
Research data for publication Julian A. J. Fells, Xiuze Wang, Steve J. Elston, Chris Welch, Georg H. Mehl, Martin J. Booth, and Stephen M. Morris, "Flexoelectro-optic liquid crystal analog phase-only modulator with a 2pi range and 1kHz switching," Opt. Lett. 43, 4362-4365 (2018) . See ReadMe file for information about the data